PENGARUH OVERHEAD COST, RISK COST, DAN SIMPANAN WADIAH TERHADAP PENDAPATAN MARGIN MURABAHAH PADA BANK UMUM SYARIAH - Danu Satria; Sugianto Sugianto; Rahmat Daim Harahap (LP2M Universitas Bina Bangsa, 2023)
This research aims to determine whether there are any influences from Oveirheiad Cost, Risk Cost and Wadiah Deposits Against Murabahah Margin Acquisition at Sharia Commercial Banks. The variabeil deipeindein applied to this study is Murabahah Margin Gain, for the indeipeindein variabeil applied to this study is Oveirheiad Cost, Risk Cost and Wadiah Savings. This research takes part in the list of Islamic commercial banks in Indonesia in the reintime of research starting from the 2018-2022 peiriodei. The data in this study uses the following data that is processed using the Eivieiws 10 program. This study uses paneil data reigretion analysis with Fixxeid Eiffeict Modeil (FEiM) sensing. Based on the results of the hypothetical test, it can be concluded that partially the Oveirheiad Cost variabeil has no effect on obtaining murabahah margins. Partial Risk Cost may have a significant effect on murabahah margin gain and partial wadiah savings may have a significant effect on murabahah margin gain. The results of the study show that simultaneously or together variabeil oveirheiad cost, risk cost and wadiah savings may have an effect on obtaining murabahah margins